2020
DOI: 10.31901/24566322.2020/31.1-3.1160
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization of Traditional Classrooms: A Students’ Perspective

Abstract: Covid-19 is fiercely hurting the field of academics and education. Millions of learners and teachers and educational institutions have been adversely affected. Educational institutions have scrapped traditional physical classroom teaching during these challenging times and have adopted e-learning models. However, there exist many discrepancies in the process of digitalization of classrooms. Therefore, this present study aims to evaluate the ramifications of the Covid-19 pandemic on the education sector and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“… Dietrich et al (2020) concluded that many of the existing approaches to education delivery were not suitable currently with generations with fewer time constraints and many sources of distraction and stress. Under new circumstances, the disruption of the educational process should find answers in targeting flexibility toward students, motivation, ethics of student assessment, and lack of access to technology ( Qiao et al, 2021 ; Ashri et al, 2020 ). According to the above, the response should integrate methodological and technological decisions while ensuring equity and transparency ( Garcia-Penalvo et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“… Dietrich et al (2020) concluded that many of the existing approaches to education delivery were not suitable currently with generations with fewer time constraints and many sources of distraction and stress. Under new circumstances, the disruption of the educational process should find answers in targeting flexibility toward students, motivation, ethics of student assessment, and lack of access to technology ( Qiao et al, 2021 ; Ashri et al, 2020 ). According to the above, the response should integrate methodological and technological decisions while ensuring equity and transparency ( Garcia-Penalvo et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“…We can state that although some studies express a preference for face-to-face learning ( Ho, Cheong & Weldon, 2021 ), online education can be just as successful and efficient in higher education. The experiences of students and faculty during the pandemic cannot be thoroughly compared to online education in the future because it was an emergent experience and was not adequately planned ( Ashri et al, 2020 ). However, given that online learning is a future direction in higher education, it is suggested that higher education institutions should invest more in online education platforms and improve faculty training plans.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation is consistent with the TAM, AR. Some found the technology to be overwhelming or distracting, and others perceived it as less useful than traditional teaching methods (Ashri, 2020).…”
Section: Attitudes Towards Armentioning
confidence: 99%